Reactive strength index: A poor indicator of reactive strength? - Healy, R.; Kenny, I. C.; Harrison, A. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To assess the relationships between reactive strength measures and associated kinematic and kinetic performance variables achieved during drop jumps. A secondary aim was to highlight issues with the use of reactive strength measures as performance indicators. Methods: Twenty-eight national- and international-level sprinters, 14 men and 14 women, participated in this cross-sectional analysis. Athletes performed drop jumps from a 0.3-m box onto a force platform with dependent variables contact time (CT), landing time, push-off time, flight time, jump height (JH), reactive strength index (RSI, calculated as JH/CT), reactive strength ratio (RSR, calculated as flight time/CT), and vertical leg-spring stiffness recorded. Results: A Pearson correlation test found very high to near-perfect relationships between RSI and RSR (r=.91-.97), with mixed relationships between RSI, RSR, and the key performance variables (men: r=-.86 to -.71 between RSI/RSR and CT, r=.80-.92 between RSI/RSR and JH; women: r=-.85 to -.56 between RSR and CT, r=.71 between RSI and JH). Conclusions: The method of assessing reactive strength (RSI vs RSR) may be influenced by the performance strategies adopted, that is, whether athletes achieve their best reactive strength scores via low CTs, high JHs, or a combination. Coaches are advised to limit the variability in performance strategies by implementing upper and/or lower CT thresholds to accurately compare performances between individuals.